2016
DOI: 10.1016/j.ejca.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal bevacizumab for control of malignant ascites due to advanced-stage gastrointestinal cancers: A multicentre double-blind, placebo-controlled phase II study – AIO SUP-0108

Abstract: Purpose: Malignant ascites is debilitating for patients with advanced cancer. As shown previously, tumour cell production of vascular endothelial growth factor might be a major cause of the formation of malignant ascites. Intraperitoneal bevacizumab could therefore be an option for symptom control in refractory ascites. Patients and methods: Patients with advanced gastrointestinal cancer and malignant ascites who had undergone paracentesis at least twice within the past 4 weeks were randomly assigned in a 2:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Different studies have also shown that bevacizumab was effective in preventing intraperitoneal adhesion formation, both macroscopically and microscopically 16,28 . Recently, intraperitoneal bevacizumab was reported to be well tolerated but not effective in symptom control of gastrointestinal malignancyrelated ascites 29 . They reported that intraperitoneal bevacizumab is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have also shown that bevacizumab was effective in preventing intraperitoneal adhesion formation, both macroscopically and microscopically 16,28 . Recently, intraperitoneal bevacizumab was reported to be well tolerated but not effective in symptom control of gastrointestinal malignancyrelated ascites 29 . They reported that intraperitoneal bevacizumab is safe.…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumors, malignant pleural effusion is known to result from the elevation of the serum level of VEGF, and the inhibition of VEGF by its antibody, bevacizumab, which prevents the accumulation of VEGF ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is a recombinant humanized monoclonal antibody that inhibits the biological activity of VEGF. A number of small studies have reported on the safety and efficacy of intraperitoneal (IP) administration of bevacizumab (BVZ) for the treatment of malignant ascites to date with mixed results …”
Section: Patient Characteristicsmentioning
confidence: 99%